Bioinspired Superhydrophobic Highly Transmissive Films for Optical Applications. Issue 44 (26th September 2016) - Vüllers, Felix; Gomard, Guillaume; Preinfalk, Jan B.; Klampaftis, Efthymios; Worgull, Matthias; Richards, Bryce; Hölscher, Hendrik; Kavalenka, Maryna N.
Abstract : Inspired by the transparent hair layer on water plants Salvinia and Pistia, superhydrophobic flexible thin films, applicable as transparent coatings for optoelectronic devices, are introduced. Thin polymeric nanofur films are fabricated using a highly scalable hot pulling technique, in which heated sandblasted steel plates are used to create a dense layer of nano‐ and microhairs surrounding microcavities on a polymer surface. The superhydrophobic nanofur surface exhibits water contact angles of 166 ± 6°, sliding angles below 6°, and is self‐cleaning against various contaminants. Additionally, subjecting thin nanofur to argon plasma reverses its surface wettability to hydrophilic and underwater superoleophobic. Thin nanofur films are transparent and demonstrate reflection values of less than 4% for wavelengths ranging from 300 to 800 nm when attached to a polymer substrate. Moreover, used as translucent self‐standing film, the nanofur exhibits transmission values above 85% and high forward scattering. The potential of thin nanofur films for extracting substrate modes from organic light emitting diodes is tested and a relative increase of the luminous efficacy of above 10% is observed. Finally, thin nanofur is optically coupled to a multicrystalline silicon solar cell, resulting in a relative gain of 5.8% in photogenerated current compared to a bare photovoltaic device. Abstract : Superhydrophobic highly transmissive polymeric films inspired by hair‐covered plant surfaces are fabricated using a scalable hot pulling technique. The flexible self‐cleaning films are characterized by low reflection, high transmission, and high amount of forward scattering. These exceptional optical properties are exploited for improving the efficiency of organic light‐emitting diodes and silicon‐based solar cells.